2019
DOI: 10.1021/acs.macromol.9b00091
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Mono-, Bi-, and Trimodal Molar Mass Distributions and All-Hydrocarbon Composites by Ethylene Polymerization on Bis(imino)pyridine Chromium(III) Supported on Ultrathin Gibbsite Single Crystal Nanoplatelets

Abstract: Multimodal molar mass distributions (MWD) of high-density polyethylene (HDPE) were tailored either by reactor cascade technology using a chain transfer agent or by multisite polymerization catalysis combining different single-site catalysts on the same support in a single reactor. Herein,2,6dimethylphenylimino)ethyl]pyridine chromium(III) (CrBIP) is supported on methylaluminoxane (MAO)-tethered ultrathin γ-Al(OH) 3 (gibbsite) single crystal nanoplatelets to produce reactor blends of HDPE wax and higher molar m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The DCSs show one melting isotherm, like is typical for in situ blends with single supports [49,[67][68][69]. The thermal properties of the polymer are typical for not (fully) entangled UHMWPE [61]. The pristine material had a first (standard) melting point of 142.1 • C and a high degree of crystallinity of 73 % [27,70].…”
Section: Catalyst Synthesis and Product Characterizationmentioning
confidence: 92%
See 1 more Smart Citation
“…The DCSs show one melting isotherm, like is typical for in situ blends with single supports [49,[67][68][69]. The thermal properties of the polymer are typical for not (fully) entangled UHMWPE [61]. The pristine material had a first (standard) melting point of 142.1 • C and a high degree of crystallinity of 73 % [27,70].…”
Section: Catalyst Synthesis and Product Characterizationmentioning
confidence: 92%
“…Thus, the typical reactor blends of HDPE/UHMWPE were obtained with only one catalyst in form of 1 [9,16,[60][61][62]. The ratio of HDPE to UMWPE would be adjustable by the reaction time or TEA concentration, however, this was not pursued here [63].…”
Section: Catalyst Synthesis and Product Characterizationmentioning
confidence: 99%
“…Over the recent years, the multisite catalyst technology has been proposed by researchers to immobilize homogeneous active sites on different supports comprising MgCl 2 , silica, and graphene [7][8][9][10]. In this technology generally two or three different types of metallocenes and post-metallocene catalysts are immobilized on one or more preferred kinds of supports [8,[10][11][12][13][14]. As a consequence, polymers produced using multi component catalysts exhibit multi modal molecular weight distribution [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, polymers produced using multi component catalysts exhibit multi modal molecular weight distribution [7]. A series of multisite catalysts were developed by Mülhaupt and Co-workers in which bimodal or trimodal polyethylene possessing precisely controlled microstructures are obtained [8,[10][11][12][13][14][15][16][17][18] One of their outstanding results, was the successful development of a polyethylene additive, that caused significant improvement in HDPE mechanical properties. The polymer stiffness, toughness and tensile strength were increased simultaneously, in terms of tensile strength (+ 392%), impact resistance (+ 197%) and Young's modulus (+ 365%) [8].…”
Section: Introductionmentioning
confidence: 99%
“…34 Recently, Mulhaupt and co-workers demonstrated that by varying the amount of methylaluminoxane (MAO) used to immobilize a chromium catalyst, distinct MWDs could be obtained. 35 A conceptually similar approach would be to create a support with a range of sites, so that one metallocene might behave in very different ways when immobilized on the surface. A classical support for immobilizing metallocenes is silica, often by using MAO as a cocatalyst.…”
mentioning
confidence: 99%